Evaluation of Organic, Food-Grade Hydrophobic Coatings for Suppressing Oviposition and Increasing Mortality of Western Cherry Fruit Fly (Diptera: Tephritidae). Issue 4 (24th May 2022) - Yee, Wee L; Kaiser, Clive
Abstract: Newer organic options for protecting fruit from tephritid fruit fly attack are needed to reduce extensive insecticide use. Here, we evaluated organic, food-grade hydrophobic coatings that help protect sweet cherries ( Prunus avium L.) from water-induced cracking for suppressing attack on cherries by western cherry fruit fly, Rhagoletis indifferens Curran (Diptera: Tephtitidae), as well as for their effects on fly mortality. Three formulations of coatings called HydroShield 13.20, 13.22, and 13.28 that form invisible elastic barriers on cherries and that consist of complex carbohydrates, fatty acids and occlusive agents, solvents, emulsifiers, emollients, surfactants, and other ingredients were tested. In the laboratory, fly visits on and oviposition in HydroShield-coated cherries were 66.1–92.8% and 59.1–99.5% lower, respectively, than in controls. The mean number of dead female flies exposed to HydroShield-coated cherries was 69.4–94.6% greater than of females exposed to control cherries. In the field, three sprays of HydroShield 13.22 and 13.20 on sweet cherry trees in 2020, when fly densities were high, reduced larval infestations in cherries by 32.1% and 31.8%, respectively. In the field in 2021, when fly densities were lower, three sprays of HydroShield 13.22 and 13.28 reduced infestations in cherries by 90.5% and 86.8%, respectively, but sprays also reduced cherry size and toughened cherries. HydroShield formulations show promise in protecting sweet cherry from attack by R . indifferens, but further testing is needed to improve formulations so that they suppress fly oviposition without affecting cherry quality.